Hospital Costs of Injection Drug Use in Florida. (11th September 2020) - Coye, Austin E; Bornstein, Kasha J; Bartholomew, Tyler S; Li, Hua; Wong, Stanley; Janjua, Naveed Z; Tookes, Hansel E; St Onge, Joan E
Abstract: People who inject drugs (PWID) experience significant injection-related infections (IRIs) at significant healthcare system cost. This study used and validated an algorithm based on the International Classification of Diseases, Tenth Revision, to estimate hospitalized PWID populations, assess the total statewide morbidity for IRIs among PWID, and calculate associated costs of care.